2022
DOI: 10.1017/wsc.2022.61
|View full text |Cite
|
Sign up to set email alerts
|

Herbicides in unexpected places: non-target impacts from tree root exudation of aminopyralid and triclopyr following basal bark treatments of invasive chokecherry (Prunus padus) in Alaska

Abstract: Basal bark treatment of invasive trees is an approach designed to limit damage to non-target vegetation in the vicinity, but non-target injury is still documented. No study of basal bark treatments has examined the release of herbicide residues from roots of treated plants and resulting non-target impacts. Studies were conducted in Alaska interior and coastal boreal forests on basal bark treatments with aminopyralid and triclopyr on active growth and dormant invasive chokecherry (Prunus padus L.). The study as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Although we only tested the triclopyr acid formulation, results are in agreement with previous investigations of root exudation of the butoxyethyl ester formulation. These concluded it is limited and unlikely to result in non-target injury (Eck and McGill 2007; Graziano et al 2022; Harrington et al 2016; Kochenderfer 1999). Additionally, although not part of this study, the transfer of herbicides from target plants to non-target vegetation through interspecific root grafting is also rare and has not been observed with triclopyr (Eck and McGill 2007; Futch and Weingarten 2010; Kochenderfer et al 2006; Willoughby 1999).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Although we only tested the triclopyr acid formulation, results are in agreement with previous investigations of root exudation of the butoxyethyl ester formulation. These concluded it is limited and unlikely to result in non-target injury (Eck and McGill 2007; Graziano et al 2022; Harrington et al 2016; Kochenderfer 1999). Additionally, although not part of this study, the transfer of herbicides from target plants to non-target vegetation through interspecific root grafting is also rare and has not been observed with triclopyr (Eck and McGill 2007; Futch and Weingarten 2010; Kochenderfer et al 2006; Willoughby 1999).…”
Section: Resultsmentioning
confidence: 99%
“…We recommend the use of triclopyr for basal bark treatments when non-target injury must be avoided. However, land managers should anticipate greater triclopyr release and an elevated risk for non-target injury when performing basal bark treatments in high-density plant infestations, due to increased herbicide output (Graziano et al 2022). We recommend that future research should focus on investigating alternative mechanisms of non-target injury that remain untested for triclopyr, as well as approaches that seek to improve triclopyr herbicide stewardship in basal bark treatments.…”
Section: Root Exudation Studymentioning
confidence: 99%
See 1 more Smart Citation
“…Likewise, triclopyr amine salt (found in Garlon 3A) has persisted in soil up to a year after treatment on silt clay loam soils [27]. Graziano et al [5] found a limited amount of non-target chokecherry damage associated with triclopyr treatments (only 5% of treatments) found in soil residue, where as, aminopyralid (residual soil active herbicide) was found in 57% of field treatments. The study also stated that non-treatment soils had greater plant dry mass compared to soils with herbicide treated trees.…”
Section: Discussionmentioning
confidence: 99%
“…Eck [3] did not observe any damage (wilting, axillary budding, chlorosis, and necrosis) to adjacent stems within treatments using triclopyr as basal bark applications (Garlon 4 ® ) or stem injection using triclopyr (amine formulation) capsules. Limited flashback damage (5% of treatments) of triclopyr ester (Garlon 4®) into non-target stems was observed by Graziano et al [5]. Turner et al [6] found that a combination of triclopyr amine (50%), water (40%), and imazapyr (10%) gave better control of more species compared to triclopyr (amine) alone in older stands.…”
Section: Introductionmentioning
confidence: 96%